Rapid detection of grass carp reovirus type 1 using RPA-based test strips combined with CRISPR Cas13a system - Li, Huaming; Cao, Xinyue; Chen, Ruige; Guang, Min; Xu, Mengran; Wu, Xiaomin; Yang, Rongrong; Lei, Liancheng; Zhang, Fuxian (Frontiers in Microbiology, 2023)
Introduction Due to the existence of grass carp reovirus (GCRV), grass carp hemorrhagic disease occurs frequently, and its high pathogenicity and infectivity are great challenges to the aquaculture industry. As a highly pathogenic pathogen, the outbreak of hemorrhagic disease often causes tremendous economic losses. Therefore, it is important to rapidly and accurately detect GCRV on site to control timely. Methods In this study, recombinant enzyme amplification (RPA) combined with clustered regularly interspaced short palindromic repeats (CRISPR)/Cas13a system was employed to establish a method to detect the vp7 gene of grass carp reovirus type 1. This method can be adopted for judging the results by collecting fluorescence signal, ultraviolet excitation visual fluorescence and test strip. Results Combined with the RPA amplification experiment, the detection limit of the RPA-CRISPR method can reach 7.2 × 101 copies/μL of vp7 gene per reaction, and the detection process can be completed within 1 h. In addition, this method had no cross-reaction with the other 11 common aquatic pathogens. Then, the performance of the RPA-CRISPR/Cas13a detection method was evaluated by comparing it with the real-time fluorescence quantitative PCR detection method of clinical samples. The results of RPA-CRISPR/Cas13a detection were shown to be in consistence with the results obtained from the real-time fluorescence quantitative PCR detection. The coincidence rate of this method with 26 GCRV clinical samples was 92.31%. Discussion In summary, this method has high sensitivity, specificity and on-site practicability for detecting GCRV type 1, and has great application potential in on-site GCRV monitoring.